África “na pasajen” identidades e nacionalidades guineenses e cabo-verdianas - Mourão, Daniele Ellery (2006)
The goal of this work is to comment the concepts of identity and nationality as they have been formulated by guineans and cape verdians professionals taking part at PEC-G e PEC-PG programs in Brazil. From a theoretical point of view, focus has been given to the identity concept formulated by Manuela Carneiro da Cunha, as a strategy of difference, from relational and situational perspectives, as well as of manipulation of its own differences. In terms of nationality, the concept of nation is considered as not restricted to territory, language, religion or race, even if all these reference points contribute in building a national identity. Quoting Benedict Anderson, nationality is the feeling of belonging to a certain nation, trough shared customs, values, beliefs and daily practices with the collectivity. By interviewing guineans and cape verdians professionals trained in Brazil, distinctive processes of renewed significations of cultural (ethnic) and national identities have been identified in both African countries, allowing them different approaches in entering the “democratic model” of nation-state. Guinea and Cape Verde are very close to each other geographically speaking, and share a history of political struggle. But the two countries were subjected to different models of colonization, which promoted the building of distinct national identities. The colonizer established many distinctions between guineans “natives” and “colonized” cape verdians. It produced several conflicts between them, to be ended only during the independency process from Portugal, when a bi-national state was formed embracing both countries. For some time, they shared the same party and national anthem. To favour the union, guineans and cape verdians manipulated their own national identities to reduce their differences in race, religion, cultural tradition, values and beliefs. But differences and disagreements would prevail to this union, with conflicts between the ruling classes finally separating the two countries. This work emphasizes the deconstruction of the notion of the African continent considered as a homogeneous whole. It questions the concepts of nation and nationality presented by the West, revealing political and economical intentions underneath these ideas, showing that they are socially built by certain groups with strategic interests in the matter. Finally, within the case under study, it shows how the educational system played a crucial role in disseminating western values linked to the modern concept of nation in European colonies.